2021
DOI: 10.1061/(asce)co.1943-7862.0002105
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Occupational Fatal and Nonfatal Injuries in Electrical and Mechanical Specialty Contracting Sectors: Necessity for a Learning Investigation System

Abstract: The specialty electrical and mechanical contracting sectors provide crucial services and perform functions that are vital to the products delivered by the construction industry. The main purpose of this study is to investigate the causes of fatal and nonfatal injuries in these specialty construction sectors over time as well as their effects on the level of safety performance in the industry. Accordingly, the most prevalent causes of fatal and nonfatal incidents in the mechanical and electrical sectors are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Identifying the measures that are predictive of safety performance is crucial to evaluating workforce safety performance. To effectively perform this task, effective safety values, practices, and responsibilities were identified in several studies [3,5,11,12,15,20,26,[33][34][35]. For instance, Abudayyeh concluded that weekly working hours, safety budget, and dedication to safety regulations are essential indicators for an effective safety system [3].…”
Section: Workforce Safety Measures In the Construction Industrymentioning
confidence: 99%
“…Identifying the measures that are predictive of safety performance is crucial to evaluating workforce safety performance. To effectively perform this task, effective safety values, practices, and responsibilities were identified in several studies [3,5,11,12,15,20,26,[33][34][35]. For instance, Abudayyeh concluded that weekly working hours, safety budget, and dedication to safety regulations are essential indicators for an effective safety system [3].…”
Section: Workforce Safety Measures In the Construction Industrymentioning
confidence: 99%
“…The analysis of the evolution of the ADSL for severe accidents due to indirect electrical contact in Spain during the study period shows that the highest year-on-year ADSL for this type of accident is observed in the secondary sector (143,58), followed by the tertiary sector (64,96) and the primary sector (54,43). However, in the previous analysis of total electrical accidents nationwide, the ADSL in the primary sector was higher than the other sectors, mainly because this type of accident did not occur in several of the years studied.…”
Section: Severe Accidents Due To Indirect Electrical Contactmentioning
confidence: 99%
“…The main objective of this study is to determine the impact and seriousness of occupational accidents in different economic sectors. Given the seriousness of injuries caused by accidents due to electrical contact [40][41][42][43], we have included this type of accident in our analysis in order to verify whether its consequences are the same or equivalent in different economic sectors.…”
Section: Introductionmentioning
confidence: 99%